1995
DOI: 10.1002/cne.903610210
|View full text |Cite
|
Sign up to set email alerts
|

Spinovestibular projections in the rat, with particular reference to projections from the central cervical nucleus to the lateral vestibular nucleus

Abstract: Projections from the spinal cord to the vestibular nuclei were examined following injections of Phaseolus vulgaris-leucoagglutinin, cholera toxin subunit B, or biotinylated dextran at various levels of the spinal cord in the rat. Labeled terminals were abundant after injections of the tracers into the C2 and C3 segments containing the central cervical nucleus. Labeled terminals were seen in the descending vestibular nucleus and the parvocellular, magnocellular, and caudal parts of the medial vestibular nucleus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 56 publications
1
18
0
Order By: Relevance
“…Retrograde labelling studies showed that spinovestibular projections to MVN and IVN originate predominantly from the central cervical nucleus, at level C1-C3, in rats (Bankoul and Neuhuber, 1992). Recently, an abundant projection from C2-C3 levels to LVN was also shown (Matsushita et al, 1995). The present results establish that sensory information reaching the VN originates not only from hindlimbs, forelimbs, and neck, but also by the way of the trigeminal complex, from the face.…”
Section: Projections From the Trigeminal Complex To The Vestibular Nusupporting
confidence: 59%
See 3 more Smart Citations
“…Retrograde labelling studies showed that spinovestibular projections to MVN and IVN originate predominantly from the central cervical nucleus, at level C1-C3, in rats (Bankoul and Neuhuber, 1992). Recently, an abundant projection from C2-C3 levels to LVN was also shown (Matsushita et al, 1995). The present results establish that sensory information reaching the VN originates not only from hindlimbs, forelimbs, and neck, but also by the way of the trigeminal complex, from the face.…”
Section: Projections From the Trigeminal Complex To The Vestibular Nusupporting
confidence: 59%
“…Recent investigations show that vestibulospinal neurones are of small size (Matsushita et al, 1995). Some of these neurones project to the central cervical nucleus (Donevan et al, 1990) and are located in the vestibular region receiving projection from the central cervical nucleus (Matsushita et al, 1995). Therefore, this similar spatial overlap supports the existence of functional reciprocal trigemino-vestibulo-trigeminal and spino-vestibulo-spinal loops which may be primarily concerned with the integration of face and neck functions.…”
Section: Functional Implicationsmentioning
confidence: 72%
See 2 more Smart Citations
“…Vestibulospinal neurons project to the contralateral CeCv (Carleton and Carpenter, 1983;Donevan et al, 1990), this connection serves for the tonic neck (cervicovestibulospinal) reflex (Matsushita et al, 1995). Projections from upper cervical segments to lateral, medial and descending vestibular nuclei also originate from the CeCv (Carleton and Carpenter, 1983;Bankoul and Neuhuber 1992;Matsushita et al, 1995;Xiong and Matsushita, 2001). Projections from upper cervical segments to lateral, medial and descending vestibular nuclei also originate from the CeCv (Carleton and Carpenter, 1983;Bankoul and Neuhuber 1992;Matsushita et al, 1995;Xiong and Matsushita, 2001).…”
Section: Central Cervical Nucleusmentioning
confidence: 99%